Secondary school teachers’ perceptions of STEM pedagogical content knowledge - Rahman, Noor Anita; Rosli, Roslinda; Rambely, Azmin Sham; Siregar, Nur Choiro; Capraro, Mary Margaret; Capraro, Robert M. (Journal on Mathematics Education, 2022)
Preparing students with knowledge and expertise in science, technology, engineering, and mathematics (STEM) is vital in meeting the demand for digital age career opportunities. Nevertheless, there is sparse research on teachers' views of student preparedness and teachers' knowledge of STEM in classroom instruction. The present study examines secondary school teachers' perceptions of STEM pedagogical content knowledge (STEMPCK). An online survey was administered to 66 Malaysian secondary school teachers through Google Forms to determine their perspectives of STEMPCK. Data were collected and analyzed using IBM SPSS Statistics Version 20.0. The descriptive analysis showed that the selected teachers highly agreed on the pedagogical knowledge and knowledge of 21st century skill components of STEMPCK. However, the non-parametric analysis showed no significant mean differences in STEMPCK scores based on gender, educational qualification, and teaching experience. The study's implications suggest that teachers in these fields should be equipped with the necessary knowledge to be more confident in implementing STEM teaching in their respective schools.